Multi-Scale Evaluation of Wear in UHMWPE-Metal Hip Implants Tested in a hip Joint Simulator. (December 2015) - Trommer, R.M.; Maru, M.M.; Oliveira Filho, W.L.; Nykanen, V.P.S.; Gouvea, C.P.; Archanjo, B.S.; Martins Ferreira, E.H.; Silva, Rui F.; Achete, C.A.
Abstract: Wear is a critical issue related to the performance of hip joint implants, namely for ultra-high molecular weight (UHMWPE) fabricated components. A greater knowledge and understanding of the attributes and capabilities of UHMWPE related to wear, at macro to nano scale levels, is crucial in the context of engineering design aiming the improvement of the implants' behaviour. Various multi-scale characterization techniques (gravimetry, geometrical analysis using coordinate measuring machine, profilometry, optical microscopy, scanning electron microscopy, energy dispersive spectroscopy, atomic force microscopy and Raman spectroscopy) were combined for the wear assessment of UHMWPE/metal (stainless steel and cobalt–chromium) implants tested in a hip joint simulator. The wear rate of the UHMWPE was about 48 mg/10 6 cycles, equivalent to a linear wear rate of 0.16 mm/year, independently of the femoral head material. Two main mechanisms determined polymer wear: a) abrasion, by second-body action of counterface metal asperities and by third-body debris; b) adhesion/fatigue, disclosed by micro-scale ripples, resulting from cyclic plastic strain accumulation. Going deeply into the analysis by AFM and Raman spectroscopy it was also observed that the structure of the material changes after wear but in distinct modes: the scratched areas became more crystalline while the smooth areas remained without structural modifications. Graphical abstract: Highlights: Wear rates for UHMWPE x CoCr and UHMWPE x SS pairs were around 48 mg/10 6 cycles. Both UHMWPE x CoCr and UHMWPE x SS pairs had a linear wear rate of 0.16 mm/year. Three worn morphologies were found: a pristine-like, a ripple-like and a scratched. Molecular chains orientation of UHMWPE occurred in the scratched area. Multi-scale wear insights give basis for improving design of UHMWPE cup materials.